THE INFLUENCE OF FINANCIAL KNOWLEDGE, HEDONIC LIFESTYLE AND FINANCIAL TECHNOLOGY ON FINANCIAL BEHAVIOR - Yasir Maulana; Reyhan Alfarizi; Disman (Digital Business and Entrepreneurship Journal, 2026)
This study aims to test the influence of financial knowledge, hedonistic lifestyle, and financial technology on financial Behavior. This study uses a quantitative descriptive research method. The sample in this study consisted of 98 students from Kuningan University. The data collection technique employed a questionnaire, and the measurement used an interval scale. Data analysis employed multiple regression analysis. The results of the study from the proposed hypothesis concluded that: Financial Knowledge, Hedonistic Lifestyle and Financial Technology together affect Financial Behavior. Financial Knowledge has a positive and significant effect on Financial Behavior. Hedonistic Lifestyle has a positive and significant influence on Financial Behavior. Financial Technology has a positive and significant influence on Financial Behavior. These findings imply that cognitive factors, lifestyle characteristics, and technological adoption jointly shape students’ financial decision-making. The study highlights the importance of improving financial literacy and promoting responsible use of financial technology to support healthier financial Behavior.